Research on the Construction of a Course-based System for College Student Art Groups: A Case Study of Shanxi Technology and Business College - zhao, zhen (Pacific International Journal, 2024)
This paper employs a case study approach, drawing from the experiences and achievements in curriculum development within the Shanxi Technology and Business College art troupe, to explore methods and strategies for the establishment of a curriculum-based system within college student art troupes. The development of a curriculum-based system for college student art troupes represents a significant initiative for universities to strengthen and enhance aesthetic education. It contributes to the improvement of students' aesthetic awareness and humanistic qualities while fostering well-rounded, highly qualified individuals. As one of the pioneering institutions in implementing curriculum-based art troupe development, the university plays a pivotal role in guiding and exemplifying the construction of curriculum systems within college student art troupes.